Developments for pulsed antihydrogen production towards direct gravitational measurement on antimatter. (5th October 2020) - Fanì, M; Antonello, M; Belov, A; Bonomi, G; Brusa, R S; Caccia, M; Camper, A; Caravita, R; Castelli, F; Comparat, D; Cheinet, P; Consolati, G; et al.
Abstract: A main scientific goal of the AE g ̄ IS experiment is the direct measurement of the Earth's local gravitational acceleration g on antihydrogen. The Weak Equivalence Principle is a foundation of General Relativity. It has been extensively tested with ordinary matter but very little is known about the gravitational interaction between matter and antimatter. Antihydrogen is produced in AE g ̄ IS via resonant charge-exchange reaction between cold Rydberg-excited positronium and cooled down antiprotons. The achievements for the development of a pulsed cold antihydrogen source are presented. Large number of antiprotons, necessary for a significant production rate of antihydrogen, are captured, accumulated, compressed and cooled over an extended period of time. Positronium (Ps) is formed through e + -Ps conversion in a silica porous target at 10 K temperature in a reflection geometry inside the main apparatus. The so-formed Ps cloud is then laser-excited to Rydberg levels, for the first time in a 1 T magnetic field. Consequently, a detailed characterization of the Ps source for antihydrogen production in magnetic field needed to be performed. Several detection techniques are extensively used to monitor antiproton and positron manipulations in the formation process of antihydrogen inside the main apparatus. Positronium detection techniques underwent extensive improvements in sensitivity during the last antiproton run. At the same time, major efforts to improve integrate and commission the detectors sensitive to antihydrogen production took place.